Studi Kadar Fosfat (Total, Polifosfat dan Ortofosfat) pada Daerah Aliran Sungai Lamat Kecamatan Muntilan - Marius Agung Sasmita Jati (Dinamika Lingkungan Indonesia, 2022)
Studies on phosphate levels (total, polyphosphate, and orthophosphate) have been carried out in the Lamat Muntilan watershed. A detergent is an approach to the amount of waste disposal of various types of phosphate in the Lamat river. High levels of phosphorus cause eutrophication, which can cause various human health problems. This study aims to determine the levels (total, polyphosphate, and orthophosphate) and compared rain and dry season with water quality standards that have been agreed upon nationally as well as theoretical studies on eutrophication pollution. This research uses the UV-Vis Spectrophotometer method by utilizing the interaction of ammonium tartrate and potassium antimonyl tartrate on orthophosphate ions to form phosphomolybdic acid which is then reduced by ascorbic acid to a modern blue color which is proportional to the number of orthophosphate ions. This modern blue color is measured at a wavelength of 880 nm. The result data showed that the average total phosphate levels of river water of 0.240 ppm in the rainy season and 0.204 ppm in the dry season, for polyphosphates were found at 0.032 ppm in the rainy season and 0.064 ppm in the dry season, while orthophosphate 0.051 ppm in the rainy season and 0.101 ppm in the dry season. In the dry and rainy seasons, there were specific differences between them. This level surpassed Peraturan Pemerintah Republik Indonesia Nomor 82 Tahun 2001 about concerning Management of Water Quality and Control of Pollution Water, was not suitable for consumption directly or indirectly specifically for human needs, but if it was used for animals and plants it is still feasible. The level of all phosphate species triggered the formation of eutrophication.